The levels of markers of systemic inflammatory response among patients with acute myocardial infarction and permanent premature ventricular contraction - Sid’, E. V; Yatsenko, O. V.; Сідь, Євген Володимирович; Яценко, Олег Вадимович (My University, 2021)
Purpose. To analyze the levels of markers of systemic infl ammatory response among patients with acute myocardial infarction and permanent premature ventricular contractions. Materials and methods. The study involved 351 patients with coronary artery disease (CHD): 185 patients with acute myocardial infarction with stable ST segment elevation and 91 ones with acute myocardial infarction without ST segment elevation; the control group consisted of 75 patients with angina pectoris. The sample of patients was carried out in the period from 2015 to February 2018. In the study, the ST segment elevation myocardial infarction (STEMI) group included 96 (51.9%) residents of the city and 89 (48.1%) ones of the village; the non-ST segment elevation myocardial infarction (NSTEMI) group consisted of 42 (46.2%) residents of the city and 49 (53.8%) ones of the village. The groups were comparable in the proportion of patients from the city and village. All the surveyed persons were comparable in age, social status and sex (the ratio of men and women was 4 to 1). The levels of the acute myocardial infarction biomarkers were determined at the fi rst contact. The blood was taken 24 hours after the onset of clinical manifestations of AMI to determine the biomarkers of infl ammation.
Keywords: acute myocardial infarction; acute myocardial infarction with stable ST segment elevation; inflammation; coronary heart disease; premature ventricular contractions